(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2025)
This article explores the configuration of subjectivities associated with experiences of political violence in Colombia during the 1980s and 1990s. Based on ethnographic interviews and archival analysis, it analyzes how three relatives of victims of political violence have survived the absence of their loved ones, either by assassination or forced disappearance. The research combines the reconstruction of personal narratives with a critical analysis of memory and studies on survivors of mass violence, highlighting the importance of creative strategies in the resignification of traumatic experiences. Through practices of agency and resistance, survivors have transformed senses of family loss into new forms of what we refer to here as “inhabiting the house”. The research demonstrates how these practices challenge official narratives about what it means to “be a victim” of the armed conflict and contribute to the construction of a critical and plural collective memory by survivors.